Architecture for Measuring Blade Tip Clearance and Time of Arrival with Multiple Sensors in Airplane Engines - José Miguel Gil-García; Joseba Zubia; Gerardo Aranguren (International Journal of Aerospace Engineering)
The performance of airplane engines is influenced by the performance of their bladed disks. The loads those engines are under, both internal and external, are the origin of vibrations than can jeopardize their integrity. Traditionally, monitoring of those vibrations has been circumscribed to prototyping and quality tests of manufactured disks. However, the development of nonintrusive sensors and techniques to evaluate the vibration based on those sensors opens the monitoring of full engines, even onboard, to new possibilities. In order to assess the vibrations with these techniques, several sensors should be employed. The distance from the blade tip to the casing (tip clearance) and the time of arrival of a blade in front of the sensor are two parameters that are used as a starting point to characterize the vibrations. A flexible architecture to extract these parameters from the blades of a gas turbine has been developed. The generalization of this architecture is introduced which is able to deal with several sensors simultaneously. An implementation of this architecture has been carried out employing a trifurcated optic sensor, whose working principle is explained. A study of the resources required to implement this architecture on measurements of several optic sensors simultaneously and in parallel is presented. The architecture and measurement method have been validated using signals recorded during the test of the compressor stage with 146 blades on a turbine rig.